Subgroup-Independent Mapping of Renal Cell Carcinoma—Machine Learning Reveals Prognostic Mitochondrial Gene Signature Beyond Histopathologic Boundaries - Marquardt, André; Solimando, Antonio Giovanni; Kerscher, Alexander; Bittrich, Max; Kalogirou, Charis; Kübler, Hubert; Rosenwald, Andreas; Bargou, Ralf; Kollmannsberger, Philip; Schilling, Bastian; Meierjohann, Svenja; Krebs, Markus (Frontiers in Oncology, 2021)
Background: Renal cell carcinoma (RCC) is divided into three major histopathologic groups – clear cell (ccRCC), papillary (pRCC) and chromophobe RCC (chRCC). We performed a comprehensive re-analysis of publicly available RCC datasets from the TCGA (The Cancer Genome Atlas) database, thereby combining samples from all three subgroups, for an exploratory transcriptome profiling of RCC subgroups. Materials and Methods: We used FPKM (fragments per kilobase per million) files derived from the ccRCC, pRCC and chRCC cohorts of the TCGA database, representing transcriptomic data of 891 patients. Using principal component analysis, we visualized datasets as t-SNE plot for cluster detection. Clusters were characterized by machine learning, resulting gene signatures were validated by correlation analyses in the TCGA dataset and an external dataset (ICGC RECA-EU). Results: Many RCC samples co-clustered according to histopathology. However, a substantial number of samples clustered independently from histopathologic origin (mixed subgroup) – demonstrating divergence between histopathology and transcriptomic data. Further analyses of mixed subgroup via machine learning revealed a predominant mitochondrial gene signature – a trait previously known for chRCC – across all histopathologic subgroups. Additionally, ccRCC samples from mixed subgroup presented a weaker angiogenesis-related signature in internal (TCGA cohort) as well as external (ICGC RECA-EU cohort) validation. Moreover, mixed subgroup affiliation was associated with a highly significant shorter overall survival for patients with ccRCC – and a highly significant longer overall survival for chRCC patients. Conclusions: Pan-RCC clustering according to RNA-sequencing data revealed a distinct histology-independent subgroup characterized by strengthened mitochondrial and weakened angiogenesis-related gene signatures. Moreover, affiliation to mixed subgroup went along with a significantly shorter overall survival for ccRCC and a longer overall survival for chRCC patients. Further research could offer a therapy stratification by specifically addressing the mitochondrial metabolism of such tumors and its microenvironment.